2009
DOI: 10.1179/174328108x369071
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and control of subsurface hooks in continuous cast ultra-low-carbon steel slabs

Abstract: Subsurface hook formation during initial solidification in the continuous casting mould degrades the quality of steel slabs owing to the associated entrapment of argon bubbles and non-metallic inclusions. To minimise hook depth and to improve slab quality, extensive plant experiments were performed and analysed to quantify the effect of casting parameters on hook characteristics using the no. 2-1 caster at POSCO Gwangyang Works, Korea. The results reveal that meniscus heat flux plays an important role in contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 18 publications
(26 reference statements)
1
16
0
Order By: Relevance
“…Moreover, increased superheat would be expected to result in solidification further down the mold and a thicker liquid slag pool, which would effectively increase the rim-to-shell distance and thereby result in shallower marks. This is in agreement with the results reported by Da¨cker and Sohlgren, [30] Lee et al, [31] and Itoyama. [34] It has been proposed that d OM can be reduced by decreasing the length of the solid meniscus [32] ; this can be achieved by reducing the vertical heat transfer (i.e., improving the thermal insulation of the bed) or by controlling the metal flow in the meniscus (through metal-flow velocity reductions, i.e., electromagnetic braking, or promoting a certain flow pattern redirection, i.e., electromagnetic stirring).…”
Section: Effect Of Delayed Solidification and Superheatsupporting
confidence: 95%
See 3 more Smart Citations
“…Moreover, increased superheat would be expected to result in solidification further down the mold and a thicker liquid slag pool, which would effectively increase the rim-to-shell distance and thereby result in shallower marks. This is in agreement with the results reported by Da¨cker and Sohlgren, [30] Lee et al, [31] and Itoyama. [34] It has been proposed that d OM can be reduced by decreasing the length of the solid meniscus [32] ; this can be achieved by reducing the vertical heat transfer (i.e., improving the thermal insulation of the bed) or by controlling the metal flow in the meniscus (through metal-flow velocity reductions, i.e., electromagnetic braking, or promoting a certain flow pattern redirection, i.e., electromagnetic stirring).…”
Section: Effect Of Delayed Solidification and Superheatsupporting
confidence: 95%
“…In-plant observations agree with the latter finding. [31] This conflict can be explained by the fact that a tide change is not instantaneous and there is a period of confusion before a stable flow is achieved (for instance a downward flow for infiltration at t n start ). These periods of confused flow reduce the overall time for slag infiltration and become more important as the oscillation cycle shortens (which occurs with increased frequency despite the increase in the number of cycles per second).…”
Section: Correlation With Plant Observationsmentioning
confidence: 97%
See 2 more Smart Citations
“…Metallographic examination of ultra-low carbon steel slabs [8,[25][26] showed that the hooks were located 2-4 mm beneath the slab surface. The hooks were the most prevalent and thickest at the corner of the slab and then on the narrow surface and broad surface of the slab.…”
Section: Introductionmentioning
confidence: 99%